2018
DOI: 10.1038/s41598-018-19700-8
|View full text |Cite
|
Sign up to set email alerts
|

Implication of liver enzymes on incident cardiovascular diseases and mortality: A nationwide population-based cohort study

Abstract: Although liver enzymes, such as γ-glutamyltransferase (GGT), alanine aminotransferase (ALT), and aspartate aminotransferase (AST), have recently been suggested as risk factors for cardiovascular diseases (CVD), impact on mortality after myocardial infarction (MI) or ischemic stroke (IS) was not previously examined. Using a population-based, nationwide cohort database, we explored the implication of GGT and aminotransferases on the development of CVD and all-cause mortality during a median 9.1 years of follow-u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
61
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 48 publications
7
61
0
1
Order By: Relevance
“…There is a monotonous increase in CVD risk that is proportional to increasing levels of GGT. Importantly, a recent nationwide population-based cohort study performed in a Korean population has demonstrated that, among liver enzymes, GGT was the most strongly implicated in the development of CVD and all-cause mortality [34], keeping in line with our current finding. Altogether, apart from liver diseases, accumulating evidence has shown that GGT is a risk indicator for hypertension [21,[35][36][37][38].…”
Section: Discussionsupporting
confidence: 92%
“…There is a monotonous increase in CVD risk that is proportional to increasing levels of GGT. Importantly, a recent nationwide population-based cohort study performed in a Korean population has demonstrated that, among liver enzymes, GGT was the most strongly implicated in the development of CVD and all-cause mortality [34], keeping in line with our current finding. Altogether, apart from liver diseases, accumulating evidence has shown that GGT is a risk indicator for hypertension [21,[35][36][37][38].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, increased ALT, GGT and ALP, which were closely associated with liver fat deposition, were considered as indices of liver injury [14][15][16][17]. As mentioned earlier, ALT can serve as an index of hepatocyte death and an indirect maker of liver injury [15,18].…”
Section: Discussionmentioning
confidence: 96%
“…[13]. Furthermore, the elevation of ALT, GGT and ALP were closely related to liver fat deposition and were considered to be an indicator of liver injury [14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%